Evaluation of Reproductive Hormones in Patients with ?-Thalassemia Major in Misan Province, Iraq (Medico Legal Update, 2020)
Assessment of serum ferritin, FSH, LH, estradiol, testosterone levels in ?-thalassemia major patients. A total50 (30 male and 20 female) children with ?- thalassemia major patients with ages range 11- 16 years and 50age and sex matched healthy adolescents as control group were included in this study. The study subjectsdivided into 2 more subgroups: 11-13 years, and 14-16 years to measure mean serum ferritin, FSH, LH,testosterone, estradiol hormones. There was significant increase (P 0.05) lowas comparedto control. In age subgroup 11–13 years, male patients have significant (P